Understanding Entrepreneurship Policy Program in Indonesia: An Analysis at Micro and Macro Level - Marsaoli, Rahmat; Kusumasari, Bevaola (Indonesian Journal of Business and Entrepreneurship, 2022)
This research aims to highlight the understanding of entrepreneurship policy implementation, particularly in Indonesia with an analysis at the micro and macro levels. Essentially, this research applied the qualitative descriptive method called document analysis from the previous study and governmental documents to gain a-detailed evidence pertaining to the entrepreneurship policy program in Indonesia. Data on entrepreneurial policy program planning, the National Long-Term Development Plan, and program reports were acquired from the Ministry of National and Development Planning 2005-2025. The findings of this research illustrate the 10 entrepreneurship policy programs at the implementation stages. It can be drawn that the entrepreneurship policy is fundamentally aimed at increasing the number of aspiring entrepreneurs or new ventures. The practical implication of this study resulted from the two different program implications at stages of analysis of Micro and Macro. Brought together, its implementation at the micro level is still primarily based on the creation of skills that could adequately cover managerial, business industry, and technical communication technology; motivation that covers incubators or mentoring programs, and greater exposure; which covers opportunity, visibility, also access to market, business and finance. Meanwhile, the analysis at the macro level resulted that government policy largely focuses on venture capital funding, innovation and education for entrepreneurship, entrepreneurship culture, infrastructure and services of entrepreneurship and lastly professional training for trainers. Keywords: entrepreneurship, government policy program, micro, macro, Indonesia